The Effect of Organizational Culture, Work Motivation, and Work Environment on Employee Commitment of KSP Dharma Prima Kita Yogyakarta - Maria Magdalena Kurniawati; Didik Subiyanto (Universal Business and Management Review, 2025)
This study aims to examine whether there is an influence of organizational culture, work motivation, and work environment on employee commitment at KSP CU Dharma Prima Kita Yogyakarta. The population in this study were all employees at KSP CU Dharma Prime Kita Yogyakarta. The number of samples in this study were 73 respondents. The sampling technique used purposive sampling method. The research method used is quantitative with data sources in the form of primary data. The results of this study provide empirical evidence that partially the variables of Organizational Culture, Work Motivation, Work Environment have a positive and significant effect on Employee Commitment.